Successful Surgical Management of Sebaceous Gland Tumours in Dogs - Parmar, JJ; Shah, AI; Rao, Neha; Godasara, DJ; Patel, DM (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Tumors of the skin and subcutaneous tissues are most common in Veterinary practice and account for approximately one-third of all the tumors in dogs (Chikweto et al., 2011). Sebaceous hyperplasia is a most common tumor of the sebaceous gland that occurs in the old age, anywhere on the body as wart-like or cauliflower-like and can become ulcerated because of trauma, while sebaceous epithelioma occurs primarily on the head as a solitary lesion but generalized cases have been reported. The treatment of choice is surgical excision (Max’s House, 2005). This paper presents case studies of sebaceous gland tumors in two dogs.